Enlistments in the All-Volunteer Force: A Military Personnel Supply Model and Its Forecasts - Ash, J. C. K.; Udis, Bernard; McNown, Robert (American Economic Review, 1983)
One of the validity of a scientific hypothesis its forecasting accuracy. Thus one of the hypothesis that the market can be used to allocate manpower to defense, as to any other occupation, its ability to predict voluntary enlistments. In our earlier paper, a simple model of accessions and enlistments to the U.S. armed forces was estimated, the conclusion being that the allvolunteer force (A VF) is an experiment in market economics which, far from having failed, has not yet been put to the test (McNown et al., 1980, p. 130). Although one may not be particularly sanguine about the prospects for testing the market experiment itself, one can at least expose the hypothesis to further scrutiny. This paper reports the results of an accuracy analysis of forecasts generated by the model, and, since the results on the whole are encouraging and the topic remains of considerable interest to the public and to policymakers alike,1 also presents updated estimates of the personnel supply elasticities. I. A Military Personnel Supply Model